2016
DOI: 10.1016/j.celrep.2016.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Tet Enzymes Regulate Telomere Maintenance and Chromosomal Stability of Mouse ESCs

Abstract: Ten-eleven translocation (Tet) family proteins convert 5-methylcytosine to 5-hydroxymethylcytosine. We show that mouse embryonic stem cells (ESCs) depleted of Tet1 and/or Tet2 by RNAi exhibit short telomeres and chromosomal instability, concomitant with reduced telomere recombination. Tet1 and Tet2 double-knockout ESCs also display short telomeres but to a lesser extent. Notably, Tet1/2/3 triple-knockout ESCs show heterogeneous telomere lengths and increased frequency of telomere loss and chromosomal fusion. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 64 publications
(111 reference statements)
4
56
0
Order By: Relevance
“…One of the most established functions for TERRAs is their ability to interfere with telomerase function by acting as a competitive inhibitor for telomere priming 55 , leading to shortened telomeres. In addition, others have shown that decreased 5hmC in murine embryonic stem cells can also lead to telomere shortening 56 , and, as shown here, loss of MECP2 led to decreased 5hmC in hiPSCs (Fig 2). Therefore, we attempted to determine the physiological consequence of TERRA induction in the absence of MECP2.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…One of the most established functions for TERRAs is their ability to interfere with telomerase function by acting as a competitive inhibitor for telomere priming 55 , leading to shortened telomeres. In addition, others have shown that decreased 5hmC in murine embryonic stem cells can also lead to telomere shortening 56 , and, as shown here, loss of MECP2 led to decreased 5hmC in hiPSCs (Fig 2). Therefore, we attempted to determine the physiological consequence of TERRA induction in the absence of MECP2.…”
Section: Resultssupporting
confidence: 80%
“…These findings together are highly relevant as DNMT3B is a key de novo methyl transferase to create methylated DNA (5mC), which is the substrate for Tet oxigenases to create 5-hydroxmethylated DNA (5hmC), which is known to be strongly bound by MECP2 63 . Recently, another study showed that deletion of Tet enzymes, which are critical to generate the 5hmC mark, led to shortened telomeres 64,65 . These studies suggest that DNA hydroxymethylation could be important in the regulation of telomere length.…”
Section: Discussionmentioning
confidence: 99%
“…8b). We note that others have recently shown a role for TET enzymes in regulating telomere length, but these effects were only noticeable in TET double- or triple-knockout ESCs 42,43 . Together, these results suggest that fluctuations in ZSCAN4 levels caused by loss of TET1 in naive pluripotent states may have no measurable impact on telomere stability but can be deleterious in primed pluripotency.…”
Section: Resultsmentioning
confidence: 56%
“…Tet1-deficient mouse embryonic stem cells (mESCs) maintained pluripotency and were largely normal [35], whereas knockout of both Tet1 and Tet2 or three Tets in mESCs showed severe abnormalities in differentiation [36, 37]. It was also reported that knockdown of Tet1 or Tet2 minimally affects pluripotency gene Nanog mRNA expression, but knockdown of both Tet1 and Tet2 reduces Nanog mRNA expression significantly in mESCs [38] and that TET1, TET2, and TET3 are required for the expression of the tumor suppressor gene TCF21 mRNA in cancer cells [39]. Therefore, TET family members have the redundant functions for the expression of certain genes in embryogenesis and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%